Archaeological bone lipids as palaeodietary markers. (15th April 2015) - Colonese, André C.; Farrell, Thomas; Lucquin, Alexandre; Firth, Daniel; Charlton, Sophy; Robson, Harry K.; Alexander, Michelle; Craig, Oliver E.
<x xml:space="preserve">Abstract</x> Rationale Stable isotope analysis of archaeological and fossil bone samples can provide important insights into past environments, ecologies and diets. Previous studies have focused on stable carbon and nitrogen isotopes in bone collagen, or carbon isotopes in bone mineral (bioapatite). Carbon isotope analysis of lipids from archaeological bone has received much less attention, partly due to the lack of suitable methodologies allowing sufficient recovery of compounds for structural and isotopic characterisation. Here we show that lipids can be easily and reliably recovered from archaeological bone using a modified protocol, and that these provide complementary dietary information to other bone components. Methods Human and animal bones were obtained from a variety of archaeological contexts. Lipids were sequentially extracted using solvent extraction (dichloromethane/methanol), followed by acidified methanol extraction (methanol/H2SO4). The lipids were then analysed by gas chromatography/mass spectrometry (GC/MS) and gas chromatography/combustion/isotope ratio mass spectrometry (GC/C/IRMS). Results Appreciable amounts of endogenous lipid were recovered from archaeological bone. Importantly, a comparison between compound‐specific and bulk collagen isotopic data shows that archaeological bone lipids reflect dietary input and can be used to distinguish between marine and terrestrial consumers, as well as between C3 and C4 plant consumers. Furthermore, the presence of essential fatty acids directly incorporated from diet to bone may provide additional palaeodietary information. Conclusions Our findings suggest that archaeological bone lipids are a hitherto untapped resource of dietary information that offer additional insights to those gained from other isotopic analyses of bone. Copyright © 2015 John Wiley & Sons, Ltd.